Quality of Life of HIV/ADS Patients receiving HAART at Bamrasnaradura Infectious Diseases Institute - ดวนด่วน ถนอมจิตต์; ลิ้มเจริญ กรุณา (Disease Control Journal, 2009)
The objectives of this cross-sectional descriptive research were to study quality of HIV/AIDS patients’ life who receiving HAART at Bamrasnaradura Infectious Diseases Institute and to examine the association between respondents socio-demographic and quality of their life. The sample was 400 HIV/AIDS patients who receiving HAART and attending the Out Patient Department of the Institute during May 1st to June 30th, 2009. The two types of self-administered questionnaire were used to collect data from samples. The questionnaires were data of socio-demographic and WHOQOL-BREF-THAI. The statistics were frequency, percentage, mean, standard deviation, range and Pearson use to examine the association. The results showed that quality of HIV/AIDS patients’ life was reported at moderate level at 65%. The mean score was 90.36 from 130 (S.D.=12.05, Range=54-121). There was a statistically significant relationship between quality of HIV/AIDS patients’ life and their socio-demographic characteristic which were level of education, occupation, income, health insurance, duration of HIV/AIDS infection, duration of received HAART and CD4 counts after received HAART (p< 0.05). This study found many factors that had impact on quality of HIV/AIDS patients’ life. Therefore, administrative team and health team needed to assure the factors influence of quality of HIV/AIDS patients’ life especially, access to ART, encouraged of self-care that concerned in health care setting to improve the quality of their life. It would also improve the quality of health care service itself and to develop the health care workers’ competency of caring on HIV/AIDS patients